Instilling Character Education Through the Essence of Behavioral Development in Overcoming Bullying in Kindergarten - Azi Matur Rahmi; Mariana Panji Ramadhan; Asniyah Asniyah (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Bullying is a problem that can arise from an early age, including in kindergartens. This behavior can negatively impact a child's social and emotional development if not handled appropriately. This research/study aims to describe the instillation of character education through the essence of behavioral coaching as an effort to overcome bullying in early childhood. The method used is a qualitative approach with observation techniques, interviews, and documentation studies in kindergarten environments. The results of the study indicate that instilling character values ​​such as empathy, honesty, responsibility, and tolerance through habituation, role modeling, and positive reinforcement can reduce bullying behavior. In addition, the role of teachers as role models and mentors, as well as parental involvement in supporting behavioral coaching at home are important factors in the success of these efforts. Seen from habituation in fostering empathy, role modeling in developing self-control, positive reinforcement forming an attitude of mutual respect and mentoring in managing emotions